Exploring Stationhead as Digital Public Sphere: An Virtual Ethnographic Study of Music Fanbase - Fikri, Muhammad; Yudhapramesti, Pandan; Indriani, Sri Seti (Universitas Islam Negeri Raden Intan Lampung, 2025)
The advancement of digital technology has significantly transformed the music industry, changing the way musicians and fans interact. This study argues that Stationhead, an audio streaming application that enables users to host live digital radio broadcasts, serves as a vital new space for fan communication and engagement. Focusing on how Salma Salsabil (Salmine)'s fanbase uses Stationhead, the research employs a virtual ethnography method with a descriptive approach, collecting data through open-ended questionnaires from 236 active fanbase members and interviews with three administrators and seven members. The findings demonstrate that Stationhead not only enables more direct, intimate interactions between fans and musicians through live broadcast sessions, storytelling, and promotional activities, but also empowers fans as active cultural producers, strengthening emotional bonds with the artist. The application further enhances solidarity within the fanbase and facilitates collective activities, such as streaming parties, fostering a dynamic digital community.